A lyginopterid pollen organ from the upper Permian of the Dead Sea region. Issue 2 (4th March 2021) - Zavialova, Natalia; Blomenkemper, Patrick; Kerp, Hans; Hamad, Abdalla Abu; Bomfleur, Benjamin
Abstract: Here we report a pollen organ from the upper Permian of the Dead Sea region with in situ pollen showing a wall structure typical for lyginopterid seed ferns. The single specimen resembles the dispersed seed-fern pollen organs Dictyothalamus and Melissiotheca in being composed of numerous densely positioned, radiating pollen sacs that together form a characteristic honeycomb-like surface pattern. The small, rounded to oval, non-saccate cryptaperturate in situ pollen grains have a verrucate sculpture and show an alveolate wall ultrastructure with alveoli arranged in several tiers. The lyginopterids, a group of seed ferns, first appeared in the latest Devonian and were very widespread across Euramerica during the Mississippian. The group shows a clear demise in the middle and late Pennsylvanian. The youngest representatives have been reported from late Permian peat-swamps in Cathaysia. The morphology of the pollen organ, the ultrastructure of the pollen, and associated foliage present further evidence that lyginopterid seed ferns persisted until the late Permian and demonstrate that they were not restricted to peat-forming swamp environments, but that they were able to survive in drier environments.